Unusual Fusion of -Fluorinated Benzophenones under McMurry Reaction Conditions - Akhmetov, Vladimir; Feofanov, Mikhail; Ioutsi, Vitaliy; Hampel, Frank; Amsharov, Konstantin (Chemistry - A European Journal, 2019)
By exposure of -fluorinated benzophenones to McMurry reaction conditions, we have observed the remarkable formation of 9,10-diphenylanthracene derivatives. This unexpected transformation necessitates the cleavage of the exceptionally stable aromatic C-F bond under mild McMurry conditions. In this work, the condensation of several related fluorinated benzo- and acetophenones has been investigated, which allow us to propose a domino-like fusion mechanism for this unusual transformation. The scope and limitations of the fluorine-promoted benzophenone fusion are subsequently discussed.
CRIS-Team WoS Importer:2019-03-01